The Relevance of Tyler's Curriculum Development to Islamic Education 5.0 - Hermawati, Kiki Ayu; Rohmatuszahroh, Anita Intan; Afrihadi, Afrihadi; Akbar, Muhammad Fikri Rizqi; Yusuf, Muhamad Hani; Utami, Lia Dwi (Universitas Muhammadiyah Magelang, 2024)
Transformation of Society 5.0 motivate education to move toward progressive direction. Islamic Education is expected to direct students to think critically, creatively, and adaptively in facing challenges of this era. This research’s purpose is to analyze the level of relevance of Tyler curriculum model with Islamic Religious Education and its need in the era of Society 5.0. this research used literature study method by analyzing related literature sources. The result of the research shows that Tyler model, which is based on philosophical and psychological principles, gives relevant work outlines for curriculum development in the society 5.0 era. This model emphasizes on the importance of education that is responsive to the public’s needs and directs students to own social sense, critical thinking skill, and high level of literacy. It is in line with Society 5.0 requirements oriented to technological integration, IT literacy, and society-based education. This research concludes that Tyler’s model can be an effective approach in developing Islamic Religious Education toward Society 5.0, by emphasizing on religious values strengthening, intellectual capacity, and technological skills in the process of education.